Design, synthesis, and biological evaluation of novel dipeptide-type SARS-CoV 3CL protease inhibitors: Structure–activity relationship study - Thanigaimalai, Pillaiyar (Eur J Med Chem, 2013)
This work describes the design, synthesis, and evaluation of low-molecular weight peptidic SARS-CoV 3CL protease inhibitors. The inhibitors were designed based on the potent tripeptidic Z-Val-Leu-Ala(pyrrolidone-3-yl)-2-benzothiazole (8; K(i) = 4.1 nM), in which the P3 valine unit was substituted with a variety of distinct moieties. The resulting series of dipeptide-type inhibitors displayed moderate to good inhibitory activities against 3CL(pro). In particular, compounds 26m and 26n exhibited good inhibitory activities with K(i) values of 0.39 and 0.33 μM, respectively. These low-molecular weight compounds are attractive leads for the further development of potent peptidomimetic inhibitors with pharmaceutical profiles. Docking studies were performed to model the binding interaction of the compound 26m with the SARS-CoV 3CL protease. The preliminary SAR study of the peptidomimetic compounds with potent inhibitory activities revealed several structural features that boosted the inhibitory activity: (i) a benzothiazole warhead at the S1′ position, (ii) a γ-lactam unit at the S1-position, (iii) an appropriately hydrophobic leucine moiety at the S2-position, and (iv) a hydrogen bond between the N-arylglycine unit and a backbone hydrogen bond donor at the S3-position.